Purification of Pseudomonas sp. proteases through aqueous biphasic systems as an alternative source to obtain bioactive protein hydrolysates - Pillaca-Pullo O.S. (2020)
Aqueous biphasic systems (ABSs) are an interesting alternative for separating industrial enzymes due to easy scale-up and low operational cost. The proteases of Pseudomonas sp. M211 were purified through ABS platforms formed by polyethylene glycol (PEG) and citrate buffer salt. Two experimental designs 23 + 4 were performed to evaluate the following parameters: molar mass of PEG (MPEG), concentration of PEG (CPEG), concentration of citrate buffer (CCit), and pH. The partition coefficient (K), activity yield (Y), and purification factor (PF) were the responses analyzed. The best purification performance was obtained with the system composed of MPEG = 10,000 g/mol, CPEG = 22 wt%, CCit = 12 wt%, pH = 8.0; the responses obtained were K = 4.9, Y = 84.5%, PF = 15.1, and tie-line length = 52.74%. The purified proteases of Pseudomonas sp. (PPP) were used to obtain hydrolysates of Lupinus mutabilis (Peruvian lupin cultivar) seed protein in comparison with the commercial protease Alcalase® 2.4L. A strong correlation between hydrolysis degree and radical scavenging activity was observed, and the highest antioxidant activity was obtained with Alcalase® (1.40 and 3.47 ?mol Trolox equivalent/mg protein, for 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) and oxygen radical absorbance capacity, respectively) compared with PPP (0.55 and 1.03 ?mol Trolox/mg protein). Nevertheless, the IC50 values were lower than those often observed for antioxidant hydrolysates from plant proteins. PEG/citrate buffer system is valuable to purify Pseudomonas proteases from the fermented broth, and the purified protease could be promising to produce antioxidant protein hydrolysates. © 2020 American Institute of Chemical Engineers